2022
DOI: 10.1002/ldr.4555
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between soil water and plant community during vegetation succession in the restored grasslands on the Loess Plateau of China

Abstract: Plant–soil water relations are important for understanding the development of plant communities, especially in arid and semiarid areas. However, the interactions between vegetation characteristics and soil water dynamics in the restored grasslands along succession chronosequence were limitedly understood. In this study, we measured the functional traits of dominant species, plant community characteristics and soil water dynamics in grasslands restored for 5, 15, and 30 years (RG5, RG15 and RG30, respectively),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Through correlation analysis, it was found that there was a significant correlation between plant community characteristics and soil physical and chemical properties (p < 0.0.5). Among them, soil bulk density was negatively correlated with vegetation diversity, indicating that the increase of soil bulk density limited the transport of nutrients and water in soil, directly affected the absorption of nutrients by plants, and was not conducive to the growth and development of plants (Zou et al, 2023). Soil total nitrogen, soil total phosphorus and soil water content directly determine the height of vegetation and the level of biodiversity (Genga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Through correlation analysis, it was found that there was a significant correlation between plant community characteristics and soil physical and chemical properties (p < 0.0.5). Among them, soil bulk density was negatively correlated with vegetation diversity, indicating that the increase of soil bulk density limited the transport of nutrients and water in soil, directly affected the absorption of nutrients by plants, and was not conducive to the growth and development of plants (Zou et al, 2023). Soil total nitrogen, soil total phosphorus and soil water content directly determine the height of vegetation and the level of biodiversity (Genga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, a suitable hydrothermal environment was necessary for plant life activities (Yao et al, 2021). Hydrological conditions could change the direction and grade of plant succession by the available water for plant (Zou et al, 2022). Rivers not only controlled the surface water supply to plants but were also the main migration carriers of necessary nutrients for plants (Li et al, 2022a).…”
Section: Mechanisms Of Underlying Surface Factors Influencing Plant D...mentioning
confidence: 99%
“…Some studies have shown that plant characteristics (such as plant biomass, coverage, evenness, and diversity) increased after secondary succession (Fan et al, 2015;Tessema and Belay, 2017), and soil properties may increase with succession due to the increase in plant biomass (Wang et al, 2009;Zhao et al, 2019). Some researchers have shown that natural regeneration through secondary succession can restore degraded soil properties and maintain soil fertility (Li et al, , 2022Zou et al, 2022;Li et al, 2023). Soil physical-chemical properties are affected by decomposition of plant root exudates and litter decomposition matter due to vegetation growth (Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%